ASPEK ETIK DAN SISTEMIK DALAM EKONOMI DAN BISNIS ISLAM - Budi Harsanto (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2014)
The fall of Enron, Lehman Brothers and other major financial institution in the world make researchers conduct various studies about crisis. The research question in this study is, from Islamic economics and business standpoint, why the global financial crisis can happen repeatedly. The purpose is to contribute ideas regarding Islamic viewpoint linked with the global financial crisis. The methodology used is a theoretical-reflective to various article published in academic journals and other intellectual resources with relevant themes. There are lots of analyses on the causes of the crisis. For discussion purposes, the causes divide into two big parts namely ethics and systemic. Ethics contributed to the crisis by greed and moral hazard as a theme that almost always arises in the study of the global financial crisis. Systemic means that the crisis can only be overcome with a major restructuring of the system. Islamic perspective on these two aspect is diametrically different. At ethics side, there is exist direction to obtain blessing in economics and business activities. At systemic side, there is rule of halal and haram and a set of mechanism of economics system such as the concept of ownership that will early prevent the seeds of crisis. Keywords: Islamic economics and business, business ethics, financial crisis